How to create a portfolio & get hired : a guide for graphic designers and illustrators - Taylor, Fig (Laurence King Publishing, 2012)
This book shows those embarking on an illustration or graphic design career how best to put together an effective, professional portfolio. It discusses what to include and how to organize and display the work, and also advises on presentation techniques and self-promotion. Both print and digital portfolios are covered. Deciding who to approach for work is of key importance whether you are looking for a full-time position or freelance work, and the book maps out the creative marketplace, examining the main areas of work and describing the types of position available in each, and how the commiss.